Circular RNA VANGL1 Facilitates Migration and Invasion of Papillary Thyroid Cancer by Modulating the miR-194/ZEB1/EMT Axis. (8th March 2022) - Xiang, Yangfeng; Wang, Wendong; Gu, Jialei; Shang, Jinbiao
Abstract : Circular RNAs (circRNAs) are often aberrantly expressed in human tumors and also serve a critical regulatory role in papillary thyroid cancer (PTC). The aim of this study is to investigate the expression pattern and biological role of circVANGL1 in PTC. The results revealed that circVANGL1 was significantly upregulated in human PTC samples. In addition, high circVANGL1 expression was closely associated with adverse clinical parameters of PTC patients. Our in vitro experiments further indicated that the knockdown of circVANGL1 using siRNA obviously repressed migration, proliferation, EMT, and invasion of PTC cells, while opposite effects were induced by its overexpression. We further noted that circVANGL1 could interact with miR-194 directly in PTC, and serve as a ceRNA to regulate ZEB1 function. Moreover, miR-194 inhibition markedly abrogated the effects of circVANGL1 knockdown in PTC cells. Therefore, our results provide convincing evidence that circVANGL1 may exert oncogenic effects in PTC, partly via regulating the miR-194/ZEB1 axis.